TRANSITION OF MERGERS AND EMPLOYEE BEHAVIOR: A LATEST OVERVIEW OF SHARIA BANKING ORGANIZATIONS - Fitri Purnamasari; Hanjar Ikrima Nanda; Gusti B tari Artichah; Gracia Angelina Nawang Wulan; Mohd Rizal Palil (Jurnal Inovasi Penelitian, 2021)
Various kinds of strategies tend to be carried out by business people in order to maintain their business while strengthening their position among other competitors, such as carrying out strategies in the form of business combinations or mergers. However, often the merger strategy also has an impact on the internal parties of the entities that do it. This study seeks to dig deeper into the perspectives and views of employees affected by the merger, especially employees of Islamic banking entities. The research was conducted using qualitative methods. Data were collected from a number of direct and indirect interviews (through open-questionnaire) on eight employees from upper management and lower management at Bank Syariah X in Malang City. Overall, employees can be said to respond positively to the merger in Islamic banking, although there are some negative things related to welfare that they are worried about.